Spectrum utilization over licensed and unlicensed bands - Guo, Shuhang (2016)
Nowadays, telecommunication technology becomes one of the universal phenomenon used in people’s daily life. In recent years, the appearance of smartphones, tab lets, mobile Internet Apps and services led to mobile data traffic proliferating, and the devices and ser- vices will continue to increase dramatically for some time. The fact along with the tele- communication devices increasing to aggravate the overload problem is that the users seek for fast and reliable data transmission, as well as service continuity. To address the over- load issue, LTE-Unlicensed (LTE-U) turns out to be one of the reasonable solutions to provide high performance and seamless interoperability for users’ experience. This thesis includes comprehensive literature review of LTE and LTE–U technolo- gies from both operators' and users' perspective, and the analysis of their impact on the field of licensed and unlicensed spectrum. LTE and Wi-Fi coexistence mechanisms are introduced with the basic characteristics, such as time, power and frequency. Moreover, three key challenges of LTE-U are also discussed, particularly the most important issue of multiple technologies shared by the unlicensed spectrum bands. At the end of this thesis, an optimized method is analyzed and proposed to design the optimal scheme.